Interorganizational Dependence and Responsiveness to Affirmative Action: The Case of Women and Defense Contractors - Salancik, Gerald R. (Academy of Management Journal, 1979)
This study is an examination of the effect of interorganizational dependencies on compliance with government affirmative action demands. Defense contractors were the subjects in the study. The speed and affirmative action displayed by their replies were statistically related to an interaction of (1) the firm's proportion of sales to the government, (2) the proportion of a government procurement supplied by the firm, and (3) the magnitude of the firm's nondefense sales. More affirmative actions were apparent for consumer product firms, which had the least power in their exchanges with the government.